On ground states of λ-model on the cayley tree of order two - Mukhamedov, Farrukh; Pah, Chin Hee; Jamil, Hakim (IOP Publishing Ltd., 2016)
In the paper, we consider the λ-model with spin values {1, 2, 3} on the Cayley tree of order two. We describe ground states of the model.